The association between physical activity, fitness and body mass index on mental well-being and quality of life in adolescents - Eddolls, William T. B. (Qual Life Res, 2018)
PURPOSE: The purpose of the current study was to investigate the mediatory role between vigorous physical activity, body mass index (BMI), and cardiorespiratory fitness on symptoms of depression and their subsequent direct and indirect effects on quality of life (QoL). METHODS: Five hundred and seventy-six adolescents’ (314 boys, 12.5 ± 1.1 years) physical activity levels, cardiorespiratory fitness, BMI, levels of depressive symptoms, and QoL were measured. Structural equation modelling was used to evaluate the difference in linear structural associations between variables. RESULTS: The model suggested that cardiorespiratory fitness (β = 0.16, p < 0.001) and symptoms of depression (β = − 0.52, p < 0.001) were both directly associated with physical QoL, with depressive symptoms also directly influencing psychological QoL (β = − 0.79, p < 0.01). Body mass index was indirectly associated with physical QoL, mediated by both symptoms of depression (β = − 0.06, p < 0.001) and cardiorespiratory fitness (β = 0.05, p < 0.001) and psychological QoL mediated by symptoms of depression (β = − 0.09, p < 0.001). Vigorous physical activity was indirectly associated with QoL, mediated by cardiorespiratory fitness (β = − 0.04, p < 0.001). CONCLUSIONS: Models suggested that vigorous physical activity, cardiorespiratory fitness and BMI were associated, both directly and indirectly, with mental well-being and QoL. It could, therefore, be postulated that enhancing cardiorespiratory fitness and BMI through increasing vigorous physical activity may be beneficial to both mental well-being and QoL in adolescents.